Electrohydrodynamics in nanochannels coated by mixed polymer brushes: effects of electric field strength and solvent quality. (2nd February 2018) - Cao, Qianqian; Tian, Xiu; You, Hao
Abstract: We examine the electrohydrodynamics in mixed polymer brush-coated nanochannels and the conformational dynamics of grafted polymers using molecular dynamics simulations. Charged (A) and neutral polymers (B) are alternately grafted on the channel surfaces. The effects of the electric field strength and solvent quality are addressed in detail. The dependence of electroosmotic flow characteristics and polymer conformational behavior on the solvent quality is influenced due to the change of the electric field strength. The enhanced electric field induces a collapse of the neutral polymer chains which adopt a highly extended conformation along the flow direction. However, the thickness of the charged polymer layer is affected weakly by the electric field, and even a slight swelling is identified for the A–B attraction case, implying the conformational coupling between two polymer species. Furthermore, the charged polymer chains incline entirely towards the electric field direction oppositely to the flow direction. More importantly, unlike the neutral polymer chains, the shape factor of the charged polymer chains, which is used to describe the overall shape of polymer chains, is reduced significantly with increasing the electric field strength, corresponding to a more coiled structure.